The Low Countries : Arts and Society in Flanders and the Netherlands : A Yearbook 1999-2000. - Arion, Frank Martinus; Armando; Bak, Saskia; Berkouwer, Jan; Boenders, Frans, 1942-; Boer, Eugenie; Brems, Elke; Brockway, James; Claus, Hugo, 1929-2008; Colin, François; De Groot, Marijke; Decavele, Johan; et al. (Rekkem : Flemish-Netherlands Foundation Stichting Ons Erfdeel, 1999)
Armando ; Bouts, Dirk ; Bruegel, Pieter ; Bruna, Dick ; Claus, Emilio ; David, Gerard ; van Dijk, Gerrit ; van Doesburg, Theo ; Driessen, Paul ; van den Eeckhout, Gerbrandt ; Ensor, James ; Fabre, Jan ; Gabriel, Paul ; van Gogh, Vincent ; van Goyen, Jan ; Hobbema, Meindert ; Hocks, Tom ; Jenet, Johann ; de Keyser, Thomas ; van Lamsweerde, Inez ; Lastman, Pieter ; Maris, Jacob ; Masereel, Frans ; Memling, Hans ; Mondriaan, Piet ; Moroni, Giovanni Bastista ; Perret, Pieter ; Poeth, Ties ; Rembrandt ; Rogiers, Peter ; van Ruisdael, Jacob ; Schippers, Arie ; Steen, Jan ; van der Stokker, Lily ; Tuymans, Luc ; Tytgat, Edgard ; Vermeersch, Peter ; Vervisch, Godfried ; van Vliet, Ariane ; de Vries, Adriaen ; Zandvliet, Robert
Engels
boek
Keywords: België; Nederland